2022
DOI: 10.1101/2022.05.16.491111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

All Staphylococcus aureus bacteraemia strains have the potential to cause infective endocarditis: results of GWAS and experimental animal studies

Abstract: and KeywordsAimsInfective endocarditis (IE) complicates 10-20% of Staphylococcus aureus bacteraemia (SAB). We aimed to determine whether IE strains of S. aureus are genotypically different or behave differently in experimental endocarditis models as compared to non-IE SAB strains.Methods and ResultsWe conducted a genome wide association study (GWAS) of 924 S. aureus genomes from IE (274) and non-IE (650) SAB patients, and tested a subset of strains in two experimental animal models of IE, one studying the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Recently, a genome wide association study of S. aureus isolates from patients with bacteremia (non-IE) or IE showed that bacteremia isolates are indistinguishable genotypically from those that cause IE within clonal groups and have similar disease potential in experimental IE ( Bastien et al., 2022 ). Differences in gene expression that may account for strain-specific disease presentation across invasive isolates was not addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a genome wide association study of S. aureus isolates from patients with bacteremia (non-IE) or IE showed that bacteremia isolates are indistinguishable genotypically from those that cause IE within clonal groups and have similar disease potential in experimental IE ( Bastien et al., 2022 ). Differences in gene expression that may account for strain-specific disease presentation across invasive isolates was not addressed.…”
Section: Introductionmentioning
confidence: 99%